Phonological Changes in the Appropriation of English Names by Masa People (Global Journal of Human-Social Science, 2024)
This paper concerns itself with the appropriation of English proper names by the Masa people from and around Yagoua a town situated in the Far North Region of Cameroon Contact between members of this community and native English speakers has left an impact on the names of the Masa people Many English names appropriated by the Masa people display native phonological preferential changes which deserve proper attention for the linguist in general and the phonologist more specifically This study describes these changes from the perspective of phonological variation in the structure of the receptor language The study tarries on potential patterns underlying the appropriation of English proper names and the process leading to it The said process involves three major steps i e perception restructuration appropriation and lastly phonological variation It follows that Masa speakers do not replicate the perceived foreign sound but restructure and or reorganize the names to suit the sound system of their native language
Keywords: english; proper names; masana; restructuration; appropriation